Multimodal Magnetic Resonance Imaging Quantification of Brain Changes in Progressive Supranuclear Palsy. Issue 1 (11th November 2019) - Pyatigorskaya, Nadya; Yahia‐Cherif, Lydia; Gaurav, Rahul; Ewenczyk, Claire; Gallea, Cecile; Valabregue, Romain; Gargouri, Fatma; Magnin, Benoit; Degos, Bertrand; Roze, Emmanuel; Bardinet, Eric; Poupon, Cyril; et al.
Abstract: Background: Progressive supranuclear palsy (PSP) is a neurodegenerative clinically heterogeneous disorder, formal diagnosis being based on postmortem histological brain examination. Objective: We aimed to perform a precise in vivo staging of neurodegeneration in PSP using quantitative multimodal MRI. The ability of MRI biomarkers to differentiate PSP from PD was also evaluated. Methods: Eleven PSP patients were compared to 26 age‐matched healthy controls and 51 PD patients. Images were acquired at 3 Tesla (three‐dimensional T1 ‐weighted, diffusion tensor, and neuromelanin‐sensitive images) and 7 Tesla (three‐dimensional‐T2 * images). Regions of interest included the cortical areas, hippocampus, amygdala, basal ganglia, basal forebrain, brainstem nuclei, dentate nucleus, and cerebellum. Volumes, mean diffusivity, and fractional anisotropy were measured. In each region, a threshold value for group categorization was calculated, and four grades of change (0–3) were determined. Results: PSP patients showed extensive volume decreases and diffusion changes in the midbrain, SN, STN, globus pallidus, basal forebrain, locus coeruleus, pedunculopontine nucleus, and dentate nucleus, in close agreement with the degrees of impairment in histological analyses. The predictive factors for the separation of PSP and healthy controls were, in descending order, the neuromelanin‐based SN volume; midbrain fractional anisotropy; volumes of the midbrain, globus pallidus, and putamen; and fractional anisotropy in the locus coeruleus. The best predictors for separating PSP from PD were the neuromelanin‐based volume in the SN, fractional anisotropy in the pons, volumes of the midbrain and globus pallidus, and fractional anisotropy in the basal forebrain. Conclusions: These results suggest that it is possible to evaluate brain neurodegeneration in PSP noninvasively, even in small brainstem nuclei, in close agreement with previously published histological data. © 2019 International Parkinson and Movement Disorder Society